Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Kinerja Karyawan PT. Jhonlin Marine Trans di Tanah Bumbu - Jayen, Fredy; Kadir, Abdul; Melania, Melania; Amrulloh, Rifqi; Erwinda, Ulivia (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2023)
The aim of this research is to test and analyze the influence partially and simultaneously Organizational Culture and Work Environment on the performance of employees PT. Jhonlin Marine Trans, Tanah Bumbu Regency. This type of explanatory research is intended to explain the relationship, difference or influence of Organizational Culture and Work Environment variables on performance variables. The population in the study were employees at the office PT. Jhonlin Marine Trans Tanah Bumbu Regency has 52 employees. The sampling technique in this study is a saturated sample, which means using the entire population in the sample as many as 52 employees. The research results explain, 1). Organizational Culture and Work Environment simultaneously influence employee performance at PT. Jhonlin Marine Trans, Tanah Bumbu Regency. 2). Organizational Culture and Work Environment partially influence employee performance at PT. Jhonlin Marine Trans, Tanah Bumbu Regency. 3). Work Environment is the dominant variable that influences employee performance at PT. Jhonlin Marine Trans, Tanah Bumbu Regency.